2017
DOI: 10.1007/s40368-017-0311-y
|View full text |Cite
|
Sign up to set email alerts
|

Best clinical practice guidance for local analgesia in paediatric dentistry: an EAPD policy document

Abstract: When considering the dental demand to treat vulnerable (medically compromised) children and adolescents in a safe, painless, less-invasive and effective way, there seems to be an urgent need to close these gaps in knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 5 publications
1
18
0
5
Order By: Relevance
“…The EAPD strongly suggests to focus on knowledge gaps regarding information on the use of LA in children aged <4 years. The EAPD further supports the statement that LA, when administered appropriately, is a safe procedure in children and adolescents with low risks of morbidity and side effects (55,131).…”
Section: Resultssupporting
confidence: 60%
“…The EAPD strongly suggests to focus on knowledge gaps regarding information on the use of LA in children aged <4 years. The EAPD further supports the statement that LA, when administered appropriately, is a safe procedure in children and adolescents with low risks of morbidity and side effects (55,131).…”
Section: Resultssupporting
confidence: 60%
“…Within the extraction procedure, the injection was most frequently reported responsible for the negative experiences. During decades, pain has been connected with dental extractions and concerned children and adolescents [17]. It could be reasoned that the injection techniques have not developed sufficiently, despite alternative anesthesia delivery methods,…”
Section: Discussionmentioning
confidence: 99%
“…To our best knowledge, IOA studies of pain felt by children have been only observational or non‐randomized comparative studies. Moreover, a recent systematic review and Evidence‐Based Clinical Practice Guidelines showed insufficient evidence supporting the injection technique as superior to others and concluded that more rigorous and high‐quality studies are needed …”
Section: Introductionmentioning
confidence: 99%
“…Local anaesthesia is frequently indicated in paediatric oral health care. 1 Two types of anaesthesia exist as follows: conventional intra-mucosal infiltration anaesthesia (CIA), frequently used by practitioners, and intraosseous anaesthesia (IOA), which delivers the local anaesthetic within the spongy bone adjacent to the tooth to anaesthetize. Needle-and injection-related fears are common sources of dental anxiety in children in case of CIA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation